Church Administration in Nigeria: Problems and Way Forward (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This paper titled: church administration in Nigeria: problems and way forward” is meant to discuss the various problems hindering effective church administration in Nigeria. The secondary data were gathered from print materials and online publications. The paper concluded poor funding, lack of current data, insecurity, government policies, corruption, poor leadership skills and disunity among Christian’s leaders have hindered effective church administration in Nigeria. Based on these problems identified, the paper hereby recommended the following; diversification of church sources of income, generation of reliable data, provision of adequate security to Churches across the Country, address issues of corruption in the church through accountability and ensure effective training for church leaders in the areas of church administration.